Kedatangan dan Perkembangan Islam ke Indonesia - Fauziah Nasution (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
There are several theories about the arrival of Islam in Indonesia. The diversity of theories is due to the phenomenon of complexity, i.e. Islam does not originate from one place/country, nor is it carried by one group of people and not at the same time. Another factor influencing the diversity of theories is the difference in evidence, elements of interest, religious subjectivity, and the ideology of historians. Although there have been conclusions about the beginning of the entry of Islam into Indonesia in 1963, the process of coming and developing Islam in Indonesia is a changing study. So there is still an opportunity to correct or strengthen an existing theory. Ulama were central actors in the early arrival and development of Islam to Indonesia. Arabic scholars who work as traders are the first group to bring and develop Islam into the territory of Indonesia, then continued by preachers from the professional Sufi circles. The figure of the Sufi cleric is strongly attached to two figures: the merchant who spreads Islam through trade as well as the heartbeat of the people's economy, and to the sultan who spreads Islam through his power. These crystallized characteristics of the propagator of Islam make Islam develop effectively. Islam was developed by Ulama through three channels namely; cultural (da'wah, education, art, culture, and marriage), structural (politics and power), economy (trade routes). In other words, the process of Islamization in Indonesia is influenced by political power and the spirit of preaching.